Estrogen Receptor β1 Expression Patterns Have Different Effects on Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors’ Treatment Response in Epidermal Growth Factor Receptor Mutant Lung Adenocarcinoma - Zhang, Lijuan; Tian, Meng; Lin, Jiamao; Zhang, Jianbo; Wang, Haiyong; Li, Zhenxiang (Frontiers in Oncology, 2021)
Estrogen receptor β (ERβ) can regulate cellular signaling through non-genomic mechanisms, potentially promoting resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs). However, the mechanisms underlying the ERβ-mediated resistance to EGFR TKIs remain poorly understood. In this study, we investigated the role of the interaction between ERβ1 and ERβ5 in non-genomic signaling in lung adenocarcinoma. We established PC9 cell lines stably overexpressing ERβ1 or ERβ1/ERβ5. Immunofluorescence revealed that ERβ5 overexpression partly retained ERβ1 in the cytoplasm. Immunoblotting analyses revealed that EGFR pathway activation levels were higher in PC9/ERβ1/5 cells than those in PC9/ERβ1 or control PC9 cells. In the presence of estradiol, PI3K/AKT/mTOR pathway activation levels were higher in ERβ1/5-expressing cells than those in ERβ1-expressing cells. Additionally, PC9/ERβ1/5 cells were less prone to the cytotoxic and pro-apoptotic effects of gefitinib compared with PC9/ERβ1 or control PC9 cells. Cytoplasmic ERβ1 was associated with poor progression-free survival in lung cancer patients treated with EGFR TKIs. These results suggest that cytoplasmic ERβ1 was responsible for EGFR TKI resistance slightly through non-genomic mechanism in EGFR mutant lung adenocarcinoma.